Preparation and application of a kind of advanced oxidation catalyst for photoinduced regulation and control of PMS activation path
Patent Information
- Application Number
- CN202611289398.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-23
AI Technical Summary
从而解决目前传统的类光芬顿处理实际复杂水体环境中活性物种不适配的问题
(1)本发明通过以管状氮化碳TCN为载体,通过原位煅烧引入CoFe2O4纳米颗粒制备得到具有限域效应的异质结CoFe2O4/TCN催化剂,增加污染物和PMS在活性位点的富集,极大地提高污染物去除效率,特别是CoFe2O4/TCN(20%),降解效率在黑暗和光照条件下达到0.15min-1,是纯CN催化剂(0.011 min-1)13.6倍,是CoFe2O4去除有机污染物的6倍。这说明通过本发明提供的技术能够大大增强污染物催化去除效率;
Smart Images

Figure CN122955508A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of advanced oxidation treatment of wastewater and photocatalytic nanocomposite materials, specifically to the preparation and application of an advanced oxidation catalyst that uses photoinduced regulation of the PMS activation pathway. Background Technology
[0002] In various water substrates, recalcitrant pollutants can damage aquatic ecosystems and threaten human health. Among numerous remediation technologies, photo-Fenton-like catalysis is a promising and future-oriented water treatment strategy. In recent years, organic pollutants such as bisphenol A (BPA) and antibiotics have been increasingly detected in different environmental media, and their potential risks to human health and ecosystems have received growing attention. By activating persulfate (PMS), photo-Fenton-like catalysis can generate a large amount of reactive oxygen species (ROS), converting recalcitrant pollutants into low-toxicity byproducts. Compared with traditional Fenton-like processes, photo-Fenton-like catalysis utilizes photogenerated carriers to regulate metal redox cycles, thereby promoting PMS activation, and has significant advantages such as high degradation efficiency, environmental friendliness, and good operational stability.
[0003] However, several key issues in actual wastewater treatment still limit its engineering application. On the one hand, the coexisting inorganic anions and natural organic matter (NOM) in actual wastewater competitively consume ROS, thereby reducing pollutant degradation efficiency. On the other hand, continuous light is a necessary condition for maintaining efficient photo-Fenton-like reactions, which also greatly limits its large-scale application. Once external light is stopped, pollutant removal will mainly rely on PMS activation initiated by classical Fenton; however, in traditional Fenton systems, it is often difficult to achieve a continuous and stable metal redox cycle, resulting in poor catalytic stability. Therefore, developing feasible photo-triggered regulation strategies to switch between free radical and non-free radical pathways to alleviate the inhibitory effects of anions and NOM is of great significance for achieving stable pollutant removal around the clock.
[0004] In-situ chemical oxidation technology based on the electron transfer pathway (ETP) has attracted widespread attention for the removal of pollutants from complex water matrices due to its advantages such as mild oxidation conditions and non-toxic end products. Meanwhile, catalysts, as electron shuttles, can maintain long-term catalytic stability. Therefore, rationally designing catalysts to achieve radical-dominated degradation under visible light and non-radical oxidation driven by ETP under dark conditions will help achieve efficient and stable water purification in all weather conditions. Thanks to its natural electron-donating properties, PMS is easily activated into free radicals in visible light-regulated metal redox cycles. However, in dark environments, traditional Fenton-like reactions preferentially occur at low-valence metal sites and activate PMS, thus severely reducing the selectivity of the ETP-dominated non-radical pathway.
[0005] In spinel metal oxides, tetrahedral sites typically exhibit redox inertness. For MOF-derived CoFe₂O₄ (CFO), tetrahedral Co sites... 2+ It exhibits redox inertness, while octahedral Fe... 3+ The lack of PMS activation capacity under dark conditions effectively addresses the low selectivity of ETP caused by the intrinsic electronic properties of PMS. Previous studies have shown that surface-adsorbed Cat-PMS* intermediates are a crucial prerequisite for ETP initiation, with high-potential Cat-PMS* directly abstracting electrons from organic pollutants, thereby initiating ETP oxidation. The confinement effect increases local reactant concentration and promotes sufficient contact between the substrate and catalytic site by restricting the bulk diffusion of PMS and pollutant molecules. This spatial confinement not only accelerates the formation of Cat-PMS* adducts in dark ETP reactions but also promotes photogenerated charge separation and inhibits carrier recombination under illumination through interface modulation and microenvironment optimization.
[0006] In summary, existing technologies have the following problems: (1) Traditional Fenton-like photocatalytic degradation systems often have fixed PMS activation pathways, making them unable to cope with complex and variable actual aquatic environments. Therefore, it is necessary to change the catalyst according to actual conditions, which leads to a significant increase in treatment costs. Complex treatment processes are not conducive to the practical application of advanced oxidation treatment technologies in the wastewater field; (2) Although metal oxides have shown certain photocatalytic PMS activation ability, spontaneous PMS activation of low-valence metal sites under dark reaction conditions can easily lead to the deactivation of active sites and the leaching of metal ions, thereby causing secondary pollution to the water environment. (3) The Fenton-like photocatalyst has a low absorption and utilization rate of visible light in sunlight, a high recombination rate of photogenerated electron-hole pairs, and a slow PMS activation rate, resulting in a still low catalytic degradation efficiency. Summary of the Invention
[0007] The specific technical problem to be solved by this invention is as follows: (1) This invention designs and constructs a novel carbon nitride-based S-type heterojunction Fenton-like photocatalyst with confinement effect. Through photo-induction, PMS can achieve free and reversible switching between free radical and non-free radical activation pathways, which is beneficial for the large-scale application of advanced oxidation treatment technology in the wastewater field. This solves the problem of the incompatibility of active species in the current traditional photo-Fenton-like treatment in the actual complex water environment.
[0008] (2) To address the problems of catalyst instability and metal ion leaching caused by spontaneous activation of PMS by low-valence metals under dark reaction conditions, this invention selects metal spinel oxide (CoFe2O4). Due to the inert reaction of the low-valence tetrahedral metal sites, leaching of metal ions under dark conditions is avoided. This also solves the problem of catalyst deactivation caused by ion leaching.
[0009] (3) Currently, the active species lifetime of Fenton-like photocatalysts is low, leading to ineffective activation of PMS and low Fenton-like photocatalytic degradation efficiency. The tubular carbon nitride-based confined catalyst material prepared in this invention can enhance the enrichment effect of PMS and pollutants under confinement, which is conducive to the mass transfer of oxide species and improves the utilization rate of PMS, thereby accelerating the reaction rate and greatly enhancing its catalytic degradation efficiency.
[0010] To address the problems in the existing technology, the technical solution adopted by this invention is as follows: The preparation and application of an advanced oxidation catalyst with photoinduced regulation of the PMS activation pathway are characterized by the preparation of a CoFe2O4 / TCN confined catalyst through melamine-assisted in-situ pyrolysis, specifically including the following steps: Step 1: Weigh 1000-1400 mg Co(NO3)2∙6H2O, 1100-1200 mg Fe(NO3)3∙9H2O, and 1800-2000 mg K3[Fe(CN)6] and dissolve them separately in deionized water. Then mix them and stir rapidly, and age at room temperature. The resulting precipitate is washed with ethanol and then dried overnight at 50-80℃ to obtain the precursor CoFe-PBA; Step 2: The dried CoFe-PBA precursor was placed in a muffle furnace and calcined in air at a certain temperature for a certain time. After holding at a certain temperature for a certain time, it was cooled to room temperature with the furnace. The resulting catalyst was named CoFe2O4. Step 3: CoFe₂O₄, urea, and melamine are mixed evenly in a certain proportion, and then thoroughly ground in a mortar for 5-20 minutes. Subsequently, the mixed powder is transferred to a 50-150 ml covered ceramic crucible and calcined at a specific temperature and heating rate under conditions of 25-35℃ and a relative humidity of approximately 65-85%. The resulting catalyst is named Y%CoFe₂O₄ / TCN, where Y represents the theoretical amount of CoFe₂O₄ added.
[0011] As an improvement, the aging time in step 1 is 20-40 hours.
[0012] As an improvement, the heating rate in step 2 is 2 °C min. -1 Calcine at 450-600 ℃ for 4 h.
[0013] As an improvement, the heating rate in step 3 is 1-5 °C min. -1 The first calcination temperature is 450-550 ℃, and the holding time is 10-50 min. The second calcination temperature is 300-400 ˚C, and the holding time is 1-5 h.
[0014] The catalyst obtained by the above preparation method can be applied in advanced oxidation-co-photocatalysis to achieve efficient removal of pollutants in complex aquatic environments by reversibly converting the PMS activation pathway through photomodulation. Beneficial effects
[0015] Compared with existing technologies, the preparation and application of an advanced oxidation catalyst for photoinduced regulation of the PMS activation pathway, as described in this invention, have the following advantages: (1) This invention prepares a heterojunction CoFe2O4 / TCN catalyst with confinement effect by introducing CoFe2O4 nanoparticles through in-situ calcination using tubular carbon nitride (TCN) as a support. This increases the enrichment of pollutants and PMS at the active sites, greatly improving the pollutant removal efficiency. In particular, the CoFe2O4 / TCN (20%) achieves a degradation efficiency of 0.15 min under both dark and light conditions. -1 It is a pure CN catalyst (0.011 min). -1 The efficiency of catalytic removal of pollutants is 13.6 times that of CoFe2O4, which is 6 times that of CoFe2O4. This demonstrates that the technology provided by this invention can significantly enhance the catalytic removal efficiency of pollutants. (2) To address the problems of metal ion escape from catalysts under dark conditions due to spontaneous Fenton reaction, which causes secondary environmental pollution, reduces catalytic activity, and exhibits poor PMS activation ability, this invention selects spinel CoFe2O4 catalyst to improve stability and conductivity. Co sites are inert sites, which can suppress spontaneous PMS activation under dark conditions, thereby reducing catalyst deactivation caused by changes in metal valence state. On the other hand, this invention constructs a confinement effect through in-situ pyrolysis to enhance interfacial PMS adsorption and form PMS*, which induces the formation of the ETP pathway under dark conditions, which is beneficial to stable operation under dark conditions.
[0016] (3) The present invention constructs a catalytic system for activating PMS to degrade organic pollutants by an advanced oxidation catalyst that uses light to regulate the PMS activation pathway. The preparation process is simple and easy, and the PMS activation pathway can be controlled by light-induced conversion, making it suitable for complex aquatic environments. Attached Figure Description
[0017] Figure 1XRD patterns of TCN and CoFe2O4 monomers prepared for different embodiments and composite CoFe2O4 / TCN catalysts with different proportions of CoFe2O4 addition; Figure 2 Monomer CN prepared by different methods x and V O -M-Co3O4 and V O -M-Co3O4@CN x Transmission electron microscopy (TEM) images of the catalyst, where (a) is Example 1, (b) is Example 2, and (c) is Example 4; Figure 3 Experimental diagram of the CoFe2O4 / TCN catalyst prepared in this invention for the photocatalytic synergistic PMS activation degradation of organic pollutants; Figure 4 The degradation spectrum and ETP current of the CoFe2O4 / TCN catalyst prepared in this invention for PMS activation degradation of organic pollutants in a two-cell experiment; Figure 5 Two-cell experimental images of the CoFe2O4 / TCN catalyst prepared in this invention for PMS activation and degradation of organic pollutants; Figure 6 The images show the UV-Vis absorption spectra (DRS) of TCN monomers and CoFe2O4, as well as the CoFe2O4 / TCN catalyst, prepared by different methods according to the present invention. Figure 7 The photocurrent response diagrams of the CoFe2O4 / TCN catalyst under different methods of the present invention are shown. Detailed Implementation
[0018] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art described herein. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0019] Example 1 Preparation of TCN catalyst Weigh 10 g of urea and 2 g of melamine into a 100 mL covered ceramic crucible, and incubate at 550 °C for 2 °C min. -1 The catalyst was synthesized under the conditions of calcination for 4 h, ambient temperature of 25-35℃, and relative humidity of approximately 65-85%. The obtained catalyst was named TCN.
[0020] Example 2 Preparation of CoFe2O4 catalyst Weigh out 1000-1400 mg Co(NO3)2∙6H2O, 1100-1200 mg Fe(NO3)3∙9H2O, and 1800-2000 mg K3[Fe(CN)6] and dissolve them separately in deionized water. Then mix and stir rapidly, and age at room temperature. The resulting precipitate is washed with ethanol and then dried overnight at 50-80℃ to obtain the precursor CoFe-PBA. The dried CoFe-PBA precursor is calcined in air at 450-600℃ with a heating rate of 2℃ / min. -1 The mixture was kept in the furnace for 4 hours, then cooled to room temperature, and finally calcined in air at a certain temperature for a certain time. The resulting catalyst was named CoFe2O4. Example 3 Preparation of 10% CoFe2O4 / TCN catalyst 10 mg CoFe₂O₄, 10 g urea, and 2 g melamine were mixed evenly in a specific ratio and then thoroughly ground in a mortar for 5-20 minutes. The resulting powder was then transferred to a 50-150 ml covered ceramic crucible and calcined at a controlled temperature and heating rate under conditions of 25-35°C and approximately 65-85% relative humidity. The resulting catalyst was named 1wt% CoFe₂O₄ / TCN.
[0021] Example 4: Preparation of 20% CoFe2O4 / TCN photocatalyst 20 mg CoFe₂O₄, 10 g urea, and 2 g melamine were mixed evenly in a certain proportion and then thoroughly ground in a mortar for 5-20 minutes. The mixture was then transferred to a 50-150 ml covered ceramic crucible and calcined at a specific temperature and heating rate under conditions of 25-35°C and approximately 65-85% relative humidity. The resulting catalyst was named 20wt% CoFe₂O₄ / TCN.
[0022] Example 5: Preparation of 30% CoFe2O4 / TCN photocatalyst 30 mg CoFe₂O₄, 10 g urea, and 2 g melamine were mixed evenly in a certain proportion and then thoroughly ground in a mortar for 5-20 minutes. The mixture was then transferred to a 50-150 ml covered ceramic crucible and calcined at a specific temperature and heating rate under conditions of 25-35°C and approximately 65-85% relative humidity. The resulting catalyst was named 30wt% CoFe₂O₄ / TCN.
[0023] Morphology and Characterization Tests: I. Material Characterization 1. XRD Analysis Figure 1 The XRD patterns of the different catalysts prepared in Examples 1-5 are shown. The crystal structure of CoFe2O4 / TCN was studied by XRD, and the diffraction peaks at 12.9° and 27.7° correspond to the (100) and (002) crystal planes of TCN, respectively. Meanwhile, characteristic diffraction peaks of the cubic phase CFO (PDF#22-1062) were observed in the composite material sample, confirming that CFO was successfully introduced into the TCN framework.
[0024] 2. Morphological Analysis like Figure 2 Image a is a TEM image of the sample prepared in Example 1, showing that the synthesized photocatalyst exhibits a unique tubular porous cross-linked structure with an outer diameter of approximately 180 nm and an inner cavity size of approximately 50 nm. This hollow tubular structure provides a nanoscale confined space, which is beneficial for the enrichment and interaction of reactants at the catalytic interface. (Comparison) Figure 2 (b) TEM images of the composite sample prepared in Example 3 show that in CFO / TCN, CFO nanoparticles are integrated into the TCN framework, thereby forming a confined heterostructure.
[0025] Performance Testing: 1. Fenton-like Photocatalytic Performance Testing Method A 250 mL double-jacketed beaker was used as the reactor for testing the pollutant degradation performance. Circulating cooling water was introduced into the jacket of the beaker to eliminate the heat generated by the light source during the catalytic reaction, thus ensuring that the photocatalytic Fenton-like performance test was conducted at room temperature and pressure. The photocatalytic performance of the CoFe₂O₄ / TCN S-type heterojunction was tested under visible light (λ≥420 nm) by BPA pollutant degradation, with air continuously pumped into the reaction system. The catalytic experiment involved adding 10 mg of photocatalyst to 100 mL of BPA solution (10 mg / L). −1 The reaction was carried out in the dark for 30 min to reach adsorption-desorption equilibrium. After adsorption equilibrium was reached, 0.6 mM PMS was added, and the light source was turned on. Every 5 min, 0.8 mL of the degradation solution was taken out, filtered through a 0.22 μm nylon membrane, and then the reaction was immediately stopped with 200 μL of methanol. During the reaction, the degradation products were analyzed using a liquid chromatography-mass spectrometry (LC-MS) system.
[0026] Figure 3 The free radical trapping diagram of the catalyst prepared in Example 4 shows that CoFe2O4 / TCN can have completely different activation pathways under visible light and dark conditions, mainly through •O2 under light conditions. ─ Free radical degradation occurs, while pollutants are primarily degraded via the ETP pathway under dark conditions.
[0027] Figure 4 and Figure 5 The two-cell experiment of the catalyst prepared in Example 4 showed that the generation of current under dark conditions was accompanied by efficient degradation of water pollutants. Figure 3 The absence of active species under dark conditions further illustrates the generation of the ETP pathway under dark conditions.
[0028] Photoelectrochemical characterization: Figure 6 The DRS diagrams of the catalysts prepared in Examples 1, 2 and 4 show that the introduction of CoFe2O4 can enhance the visible light absorption intensity of TCN, thereby improving the absorption and utilization rate of visible light in sunlight.
[0029] Figure 7 The comparison diagrams of photocurrent response of photocatalysts in Examples 1, 2, and 4 show that the CoFe2O4 / TCN photocatalyst has a higher separation and migration rate of photogenerated carriers. This indicates that the introduction of CoFe2O4 inhibits the recombination of photogenerated electron-hole pairs in TCN, and that the construction of the S-type heterojunction greatly improves the catalytic degradation efficiency of TCN.
[0030] In summary, this invention discloses a method for preparing and applying an advanced oxidation catalyst with photoinduced regulation of the PMS activation pathway. Characterization results show that tubular carbon nitride (TCN) as a support, through in-situ pyrolysis, achieves confinement of CoFe-PBA-derived CoFe₂O₄ by TCN, exhibiting extremely high stability and reusability during the reaction, and demonstrating high degradation rates under both light and dark conditions. The improved photo-Fenton-like catalytic degradation performance can be attributed to effective photogenerated charge separation and migration, as well as enhanced PMS activation ability. Furthermore, from an application perspective, unlike traditional degradation systems that rely on fixed activation pathways, CoFe₂O₄ / TCN can achieve reversible PMS activation under photoinduced conditions, greatly enhancing the catalyst's application in complex aquatic environments and possessing potential practical application value in the field of advanced oxidation wastewater treatment.
[0031] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited thereto. Any simple changes or equivalent substitutions of the technical solutions that can be obviously obtained by those skilled in the art within the scope of the technology disclosed in the present invention shall fall within the scope of protection of the present invention.
Claims
1. Preparation and application of an advanced oxidation catalyst for photoinduced regulation of the PMS activation pathway, characterized in that, The preparation of CoFe2O4 / TCN confined catalysts via in-situ pyrolysis includes the following steps: Step 1: Weigh 1000-1400 mg Co(NO3)2∙6H2O, 1100-1200 mg Fe(NO3)3∙9H2O, and 1800-2000 mg K3[Fe(CN)6] and dissolve them separately in deionized water. Then mix them and stir rapidly, and age at room temperature. The resulting precipitate is washed with ethanol and then dried overnight at 50-80℃ to obtain the precursor CoFe-PBA; Step 2: The dried CoFe-PBA precursor was placed in a muffle furnace and calcined in air at a certain temperature for a certain time. After holding at a certain temperature for a certain time, it was cooled to room temperature with the furnace. The resulting catalyst was named CoFe2O4. Step 3: CoFe₂O₄, urea, and melamine are mixed evenly in a certain proportion, and then thoroughly ground in a mortar for 5-20 minutes. Subsequently, the mixed powder is transferred to a 50-150 ml covered ceramic crucible and calcined at a specific temperature and heating rate under conditions of 25-35℃ and a relative humidity of approximately 65-85%. The resulting catalyst is named Y%CoFe₂O₄ / TCN, where Y represents the theoretical amount of CoFe₂O₄ added.
2. The preparation and application of the advanced oxidation catalyst for photo-induced regulation of the PMS activation pathway according to claim 1, characterized in that, The aging time in step 1 is 10-12 hours.
3. The preparation and application of the advanced oxidation catalyst for photoinduced regulation of the PMS activation pathway according to claim 1, characterized in that, Calcination conditions in step 2: heating rate of 2℃ / min -1 Calcine at 450-600 ℃ for 4 h.
4. The preparation and application of the advanced oxidation catalyst for photoinduced regulation of the PMS activation pathway according to claim 1, characterized in that, In step 3, the ratio of urea to melamine is 1:5 – 1:
10.
5. The preparation and application of an advanced oxidation catalyst for photoinduced regulation of the PMS activation pathway according to claim 1, characterized in that, The heating rate in step 3 is 1-5 °C / min. -1 The calcination temperature is 450-550 ℃, the holding time is 10-50 min, and the value of Y is 1-30 wt%.
6. The advanced oxidation catalyst prepared by any one of the methods in claims 1-5, which is a photo-induced controlled PMS activation pathway, is an S-type carbon nitride-based heterojunction with confinement effect, used in catalytic water treatment.